2006
DOI: 10.1227/01.neu.0000219843.34356.ee
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intracranial Hypotension Resulting in Coma: Case Report

Abstract: This case report expands the presently known clinical spectrum of this uncommon and generally benign illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…In addition to headache, neck stiffness, dizziness, nausea, vomiting, blurred vision, change in hearing, and facial numbness and weakness are occasionally experienced. Severe complications such as subdural hemorrhage, cerebral vasoconstriction, intracranial venous thrombosis, seizure, stupor, and even death have been reported [2,3,4,5,6,7]. The syndrome became well recognized after the report of pachymeningeal gadolinium enhancement in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to headache, neck stiffness, dizziness, nausea, vomiting, blurred vision, change in hearing, and facial numbness and weakness are occasionally experienced. Severe complications such as subdural hemorrhage, cerebral vasoconstriction, intracranial venous thrombosis, seizure, stupor, and even death have been reported [2,3,4,5,6,7]. The syndrome became well recognized after the report of pachymeningeal gadolinium enhancement in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Radiological features in cases with coma are subdural fluid collections/ hematoma, increasingly attenuated basilar cisterns, cerebral edema, diffuse enhancement of meninges and downward displacement of diencephalon and cerebellar tonsils. [6][7][8][9] According to Monro-Kellie hypothesis decreased cerebrospinal fluid pressure results in venous congestion resulting in enhancement of meninges or subdural collection which may cause herniation and mental decline. However, Savoiardo et al [10] reported increased diffusivity in diencephalo-mesencehalic structures by MRI in patients with brain sagging which is suggested to reflect vasogenic edema in those deep structures.…”
Section: Discussionmentioning
confidence: 99%
“…[2,7,8] Although evacuation of subdural collections provides transient improvements, this effect is not persistent. In few cases where EBP did not benefit epidural interventions like fibrin glue enjection [6] or saline infusion [3] reversed symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…15) SIH patients presenting with altered mental status or dementia often reported constant rather than orthostatic headache. 1,3,12,13,18) Such altered mental status may prevent the patients from describing the characteristics of their headache correctly. Another possibility is that SIH patients who present with altered mental status may have a larger dural hole compared with those who are neurologically intact.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11) SIH patients with concomitant CSDH seem to complain of orthostatic headache less frequently than those without CSDH. 3,13,18) Therefore, the presence of CSDH may prevent orthostatic headache from developing by correcting the abnormally low intracranial pressure (ICP) or volume. 18) In the present case, the headache was not orthostatic, so we assumed incorrectly that SDH was unrelated to SIH and performed drainage which resulted in the complication of acute SDH.…”
Section: Discussionmentioning
confidence: 99%